The Future of the Dollar - Kirshner, Jonathan; Helleiner, Eric, 1963- (Book collections on Project MUSE., 2009)
Explores possible futures of the dollar as an international currency as the dollar becomes more volatile than ever against foreign currencies, and China and the Arab Gulf states hold more United States government obligations.